Предмет: Алгебра,
автор: Ученик221603
Решите пожалуйста,а то прогулял эту тему)
Приложения:
Ответы
Автор ответа:
0
f(x) = (x² + 1)(2 - 3x)
f'(x) = (x² + 1)' * (2 - 3x) + (x² + 1) * (2 - 3x)' = 2x * (2 - 3x) - 3 * (x² + 1) =
= 4x - 6x² - 3x² - 3 = - 9x² + 4x - 3
f'(2) = - 9 * 2² + 4 * 2 - 3 = - 36 + 8 - 3 = - 31
Похожие вопросы
Предмет: Алгебра,
автор: dafil6797
Предмет: Математика,
автор: nikita880055355
Предмет: Русский язык,
автор: kov7345
Предмет: Математика,
автор: arshavin1099
Предмет: Алгебра,
автор: gerasimowsema